Arbitrary Precision Mathematica Functions to Evaluate the One-Sided One Sample K-S Cumulative Sampling Distribution - J. Randall Brown; Milton E. Harvey (Journal of Statistical Software, 2008)
Efficient rational arithmetic methods that can exactly evaluate the cumulative sampling distribution of the one-sided one sample Kolmogorov-Smirnov (K-S) test have been developed by Brown and Harvey (2007) for sample sizes n up to ﬁfty thousand. This paper implements in arbitrary precision the same 13 formulae to evaluate the one-sided one sample K-S cumulative sampling distribution. Computational experience identiﬁes the fastest implementation which is then used to calculate conﬁdence interval bandwidths and p values for sample sizes up to ten million.